The Reformation and the Idea of the North - Marshall, Peter (Nordlit, 2019)
Both scholarly and popular perceptions have identified a profound cultural and political realignment of Europe with the Reformation of the sixteenth and seventeenth centuries: a largely Protestant North confronting a predominantly Catholic South. This replaced a medieval conceptual geography of East-West, in which the North (on the basis of scriptural passages) was a zone of sinfulness and danger. This chapter argues that the emergence of a North-South cultural-religious dichotomy was more fraught and uncertain than often supposed. Late medieval North European humanists countered negative perceptions with patriotic accounts of national origins. In the era of the Counter-Reformation, British and Scandinavian Catholic exiles emphasised the intrinsic virtue and orthodoxy of northerners, and the potential for reclaiming their homelands from heresy. Protestants were often ambivalent about the North, not least since northern parts of England, Scotland, Ireland and Denmark-Norway were often associated with Catholic resistance, as well as with magic and superstition. The propaganda of the British Civil Wars reinforced both positive and negative stereotypes. While a cultural association of Protestantism with the North eventually took root, this was a contingent process, and should be seen more as a consequence than a cause of the stabilization of Europe’s confessional borders.